Mental health-related benzodiazepine use in the last 10 years: an integrative review (Research, Society and Development, 2021)
Mental health is characterized as cognitive, behavioral and emotional well-being. a state of well-being in which an individual is using benzodiazepines (BDZs) represents a critical issue as long-term treatment can lead to dependence. Thus, the research aimed to evaluate in the literature consumption of benzodiazepines related to mental health in the years 2011 to 2021. The present study is an exploratory bibliographical research of the integrative type with a qualitative nature. Individuals most at risk for BZD abuse, particularly are those with a personal or family history of substance use disorder. BZD abuse can be divided into two patterns, including deliberate or recreational abuse with the intent to get high and unintentional abuse that starts out as legitimate use but then evolves into misuse. It is critical to check mental health before prescribing, use safer alternatives, and make appropriate interventions to combat continued use.